Occurrence of ADHD in parents of ADHD children in a clinical sample - Starck M; Gruenwald J; Schlarb A (Neuropsychiatric Disease and Treatment)
Martina Starck,1 Julia Grünwald,1 Angelika A Schlarb1,21Faculty of Science, Department of Psychology, University of Tuebingen, Tuebingen, 2Department of Psychology, Faculty for Psychology and Sport Science, University of Bielefeld, Bielefeld, GermanyBackground: Despite the fact that there is a large amount of research on childhood attention deficit hyperactivity disorder (ADHD) treatment and an increasing amount of research on adult ADHD, little is known about the prevalence and influence of parental ADHD. Therefore, this study examined the frequency of parental ADHD in a clinical sample of German children suffering from ADHD. We also tried to find different levels of symptom severity for prognostic relevance. Furthermore, the association between subtypes of ADHD in children and their parents was investigated.Method: In this study, parents of 79 ADHD children were screened for ADHD according to the Diagnostic and Statistical Manual of Mental Disorders, 5th edition and International Classification of Diseases, 10th edition. The Wender Utah Rating Scale and the ADHS-Self-Report were given to 75 mothers and 49 fathers for retrospective and current symptoms. Frequency of ADHD symptoms and severity groups was calculated and relationship between parental and children’s ADHD was tested.Results: ADHD occurrence for mothers of children with ADHD was 41.3%, for fathers 51.0%. About 16.0% of the mothers had a mixed type, 9.3% had a hyperactive-impulsive subtype, and 16.0% had an inattentive subtype. Of the fathers, 18.4% had a mixed type, 10.2% had a hyperactive-impulsive subtype, and 22.4% had an inattentive subtype; 61% of the mothers and 46.9% of the fathers had low symptom severity. Medium symptom severity was reported by 37.7% mothers and 46.9% fathers, while 1.3% of the mothers and 6.2% of the fathers showed severe symptoms. No significant correlation between parental and child diagnoses was observed.Conclusion: As nearly half of the parents suffered from ADHD, these results are a matter of concern in families with ADHD children. Besides parent–child interactions, parental ADHD symptoms might influence parental education style and also effects parent training as well as the child’s therapy outcome. In the future, parents should be screened for ADHD symptoms if they or their child receive treatment and to adjust processes and design of treatment to the symptoms.Keywords: attention deficit hyperactivity disorder, adult, parents, frequency, DSM-5, ICD-10